Adult outcomes of complex pulmonary atresia, ventricular septal defect and major aortopulmonary collaterals following repair during childhood, a single centre experience. (3rd October 2022) - Chambault, A L; Drury, N E; Poole, E; Jones, T; Khan, N; Hudsmith, L; Bowater, S; Arif, S; Botha, P; Clift, P
Abstract: Background: Complex pulmonary atresia with a ventricular septal defect and major aortopulmonary collateral arteries (PA VSD MAPCA) is a rare and complex form of congenital heart disease. Staged surgical palliation is carried out in childhood, and in expert centres, is associated with good medium term survival. Adult outcomes following transition to adult care are not known. Purpose: To establish adult outcomes of PA VSD MAPCA following repair during childhood in our institution Methods: Review of clinical records for outcome data including life status, NYHA class, employment status, re-intervention in adult life, arrhythmia, pregnancy, exercise capacity and mode of death, where known. We predefined our population into two groups based on their status at transition to adult care, A) complete repair with RV-PA conduit and VSD closed and B) repaired but VSD left open. Results: 188 patients from our series have transitioned to adult services. As many were tertiary referrals (nationally and internationally) the local follow up population was 53 adults (54.7% male), mean age of those alive under follow up is 27.2±6.5 years, with a mean follow up of 25.3±6.1 years. There were 43 in group A and 10 in group B. Mortality in the total population was 18.9% (10/53), group A (16.3%), group B (30.0%), mean age at death 37.5±10.3 years and 29.9±8.4 years, 6/10 deaths were sudden. 22.6% of the whole group had DiGeorge/22q11 microdeletion, with a learning deficit in 32.7% of the cohort, where this could be assessed. Reinterventions included RV-PA conduit change, coil occlusion, pacemaker implantation, ICD implantation and ablation procedures, overall 39.6% underwent reintervention in adult life. Pregnancy occurred in 33.3% of 24 female patients. 50% of individuals were found to have undertaken some form of paid work and of these 11.5% had DiGeorge. Conclusions: Complex PA VSD MAPCA is associated with good late survival with late attrition including sudden death and heart failure. 22q11 is associated with learning deficit and consequent lack of employment. Non 22q11 have good educational outcomes and there is less observed deficit regarding employment. Successful pregnancy is possible within this population. Funding Acknowledgement: Type of funding sources: None.